The relationship between frontline nurses' psychosocial status, satisfaction with life and resilience during the prevalence of COVID‐19 disease - Mohammad Ali Zakeri; Sayed Mortaza Hossini Rafsanjanipoor; Maryam Zakeri; Mahlagha Dehghan (Wiley, 2021)
Abstract Aim The present study aimed to investigate the association between frontline nurse's psychosocial status, satisfaction with life and resilience during the prevalence of COVID‐19 disease. Design A cross‐sectional study. Methods 185 frontline nurses taking care of the COVID‐19 patients participated in the study from March to April 2020. The data were collected using demographic questionnaire, General Health Questionnaire (GHQ‐28), Generalized Anxiety Disorder 7‐item (GAD‐7), Impact of Event Scale‐Revised (IES‐R), Satisfaction with Life Scale (SWLS) and Connor‐Davidson Resilience Scale (CD‐RISC). Results The results showed that not being at risk of coronavirus infection, poor/no satisfaction with life and non‐resilience were significantly associated with higher psychological disorders. The coronavirus disease has significant consequences for the mental health of nurses. The factors affecting the mental health of nurses should be considered to support nurses in crises such as coronavirus. Provision of effective psychological interventions for nurses can be one of the effective solutions.